2014
DOI: 10.17795/semj18066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HBV Vaccination on Prevalence of Hepatitis B Virus Infection Among Volunteer Blood Donors in Tehran-Iran

Abstract: Background: Hepatitis B (HB) vaccination is the most effective measure for preventing hepatitis B virus (HBV) infection and its consequences. HB vaccination has been a part of the Expanded Program on Immunization (EPI) of Iran since 1993. To extend HBV immunization, mass HBV vaccination was planned for adolescents born during 1989-1992. Objectives: The aim of the present study was to assess the prevalence of HBV infection in Tehran blood donors after implementing national HB vaccination program. Patients and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…However, I would like to suggest for more studies in adolescents for finding the main risk factors in general population higher age than 25 years and vaccinate the adult as we did in our country before and we confirmed that strategy was effective in decreasing the HBV burden in our community [5].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…However, I would like to suggest for more studies in adolescents for finding the main risk factors in general population higher age than 25 years and vaccinate the adult as we did in our country before and we confirmed that strategy was effective in decreasing the HBV burden in our community [5].…”
supporting
confidence: 68%
“…The other studies from Tunisia in infants and children under 5 years and adolescents suggested that vertical and perinatal transmission of HBV does not appear to be significant in Tunisia [4]. However, I would like to suggest for more studies in adolescents for finding the main risk factors in general population higher age than 25 years and vaccinate the adult as we did in our country before and we confirmed that strategy was effective in decreasing the HBV burden in our community [5].…”
supporting
confidence: 66%
“… reported the risk of HBV in PWID as 21.16. Among drug‐using prisoners, age >30 years was a risk factor for HBV, which is apparently due to HBV vaccination coverage for people <30 years in Iran . Prisoners, especially those with a history of drug use, should therefore be treated as a high‐risk group in Iran that needs to be covered by HBV vaccination programmes.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the pooled estimate of HBsAg infection was higher in other E and M countries than Iran, which exhibited a prevalence of 0.58% in its blood donors, while the prevalence increased for Yemen and Djibouti, by up to 5.05% and 10.4%, respectively. This lower prevalence in Iran can be attributed to the effectiveness of the screening system, the selection of eligible donors, and the high vaccination coverage for HBV in the first years of life ( 11 , 112 ). In addition, low public awareness, particularly for the general population ( 113 ), unsafe services for blood donation ( 114 ), and a higher rate of HBsAg infection in the general population ( 115 ) may contribute to the higher prevalence of HBsAg in other E and M countries.…”
Section: Discussionmentioning
confidence: 99%